THE FACTORS INFLUENCING THE POPULARITY OF TIKTOK AMONG GENERATION Z: A QUANTITATIVE STUDY IN YOGYAKARTA, INDONESIA - Daryus , Aliyah Widyasari Putri; Ahmad , Rohizan Binti; Dada , Morakinyo (Electronic Journal of Business and Management, 2022)
TikTok has emerged as a premier social media application for sharing entertainment videos. This study examines the factors influencing TikTok's popularity, specifically focusing on how informativeness, uniqueness, co-creation, and entertainment contribute to its success. Using primary data, questionnaires were distributed to Generation Z in Yogyakarta, Indonesia, resulting in 142 respondents. The data analysis revealed that informativeness is the most significant factor related to the popularity of TikTok. Interestingly, co-creation was found to have no significant relationship with its popularity. The findings provide insights for social media managers to understand which variables to prioritize for platform growth and engagement.